Synthesis and antibacterial activity of monocyclic 3-carboxamide tetramic acids - Yong-Chul Jeong; Mark G. Moloney (Beilstein Journal of Organic Chemistry, 2013)
A chemical library of carboxamide-substituted tetramates designed by analogy with antibacterial natural products, a method for their rapid construction, and the evaluation of their antibacterial activity is reported.